Pseudepigraphic writings - Hippocrates. (Studies in Ancient Medicine, 1990)
The biography and personality of the \'Father of Medicine\' were known to the world through these important, but little studied letters and speeches. W.D. Smith here presents them newly edited from the most important manuscripts, with a facing English translation, and offers an introduction that gives a literary analysis and places them in relation to ancient history and ancient medical science. The speeches appear to be early (III B.C.) propaganda for the Island Cos, whose presence in the Library at Alexandria contributed to the characterization of the Hippocratic Corpus, while the Democritus Letters belong to the Roman period, after the firm establishment of Hippocrates' reputation.